Durio zibethinus Murr Extracts as Potential Larvacide Against Anopheles aconitus Donitz and Anopheles maculatus Theobald (Diptera: Culicidae) - Silvia Hanna Kusuma Sirait; Insar Damopolii; Regina Valentine Aydalina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Malaria is endemic in most parts of Indonesia. Anopheles aconitus and Anopheles maculatus are examples of dominant malaria vectors in Indonesia. Plant secondary metabolites can be used as malaria vector control that is safe for the ecosystem, one of which is Durio zibethinus leaves which are thought to have active compounds so that they can be used as botanical larvicides. This study aimed to determine the potency of D. zibethinus leaf extract against An. aconitus and An. maculatus and to determine the concentration, type of extract and content of secondary metabolites of D. zibethinus leaves. Determination of LC50 and LC90 using probit analysis. Maceration and remaceration were used to produce the extract and phytochemical screening to determine the active compound of D. zibethinus. The WHO insecticide bioassay testing procedure was used for the larvicide test. Ethanol extract of D. zibethinus leaf as a larvicide for An. aconitus second and third instar and larvae of An. maculatus second and third instar had LC50 ​​respectively: 480; 520; 510; and 540 ppm and LC90 respectively: 750; 760; 760; and 810 ppm. D. zibethinus leaf aqueous extract as larvicides against larvae of An. aconitus second and third instar and larvae of An. maculatus second and third instar had LC50 values ​​respectively 14,500; 16,400; 22,100; and 23,300 ppm and LC90 respectively, 26,100; 27,200; 30,600; and 33,700 ppm. Ethanol extract of D. zibethinus leaves was more effective as a larvicide. Alkaloid, saponins and tannins were found in the leaves of D. zibethinus through phytochemical screening.